Financial Distress Prediction Using the Modified Altman Z-Score Model: Empirical Evidence from Hospitality Companies Listed on the Indonesia Stock Exchange (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to evaluate the financial condition of hotel sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2023 period using the Modified Altman Z-Score model. A descriptive quantitative approach was employed to assess potential bankruptcy through the analysis of four key financial ratios: liquidity, profitability, solvency, and working capital to total assets. The findings reveal that hotel companies experienced significant financial fluctuations during the COVID-19 pandemic, with a decline in financial performance in 2021–2022 followed by a strong recovery in 2023. Most companies managed to maintain financial stability and demonstrated adaptability to changing economic conditions. Liquidity and profitability were identified as the main indicators of financial resilience, while external factors such as government policy and tourism mobility also influenced overall financial stability. The study confirms the relevance of the Modified Altman Z-Score model as a tool for predicting bankruptcy in the service sector, although its accuracy should be refined by integrating external variables to provide a more comprehensive analysis. The results of this study are expected to provide practical insights for hotel management, investors, and policymakers in developing sustainable financial strategies for the hospitality industry.